Early stent thrombosis in Kounis syndrome – a case report - Kostić, Tomislav; Perišić, Zoran; Kutlešić Kurtović, Dušanka; Maričić, Bojan; Apostolović, Svetlana; Stanojević, Dragana; Koraćević, Goran; Dakić, Sonja; Božinović, Nenad; Kostić, Katarina; Milošević, Jelena; Lazarević, Mihajlo (Vojnosanitetski pregled, 2023)
Introduction. Kounis syndrome is a simultaneous manifestation of acute coronary syndrome and conditions associated with mast cell activation, such as allergies or anaphylactic reactions. We present early stent thrombosis in a female with an atopic constitution without previous atherosclerosis of coronary arteries. Case report. A 50-year-old woman with typical anginal pain was admitted to the Clinic for Cardiology, University Clinical Center Niš. A few hours earlier, she had passed by a linden tree in bloom. She immediately felt chest pain, paresthesia and numbness in her left arm throat tightness, heaviness of the tongue, and swelling of the lips. The symptoms disappeared for 60 min after taking 10 mg of loratadine, but then they recurred. On the electrocardiographic (ECG) findings, 30 minutes after admission, ST elevation was seen in leads D2, D3, aVF, and V6. She underwent an emergency percutaneous coronary intervention procedure. Occlusive thrombosis was seen in the ostium of the left anterior descending (LAD) coronary artery. A sirolimus-coated stent was placed and thrombolysis in myocardial infarction (TIMI) 3 flow was obtained. A few hours after the intervention, the patient reported a new onset of chest pain followed by ventricular fibrillation (VF), DC shock, and the occurrence of new ST-segment elevation in aVR and V1–V3 on the ECG. Repeated angiography showed acute in-stent thrombotic occlusion. Balloon angioplasty was performed, which restored TIMI 3 flow in LAD coronary artery. Anticoagulant and corticosteroid therapy was administered. Three days after the intervention, optical coherence tomography imaging was performed, which showed good stent expansion and apposition, without atherosclerosis and thrombosis. Conclusion. Coronary angiography proved type I Kounis syndrome after exposure to an allergen, and type III Kounis syndrome developed shortly after stent placement when acute in-stent thrombosis occurred. Newly described causes of acute and subacute stent thrombosis in type III Kounis syndrome are stent-associated hypersensitivity reactions.